Mapping the functional connectivity of the substantia nigra, red nucleus and dentate nucleus: A network analysis hypothesis associated with the extrapyramidal system. (8th October 2015) - Zhang, Hong-Ying; Tang, Hui; Chen, Wen-Xin; Ji, Gong-Jun; Ye, Jing; Wang, Ning; Wu, Jing-Tao; Guan, Bing
Highlights: We firstly described the architectures of the extrapyramidal networks with resting-state functional analysis. The extrapyramidal related regions constituted a relatively exclusive network. Study on the extrapyramidal system networks has potential clinical implications. Abstract: This study aimed to examine the functional networks related to the extrapyramidal system using a temporal oscillation signal correlation analysis method based on critical nodes in the substantia nigra (SN), red nucleus (RN) and dentate nucleus (DN). Nineteen healthy subjects underwent resting-state fMRI and susceptibility weighted imaging (SWI). For the brain network analysis, the SN, RN and DN were positioned on susceptibility weighted images and used as seeds for temporal correlations analyzed via BOLD data. T -tests were performed for the correlation coefficients of each seed. We demonstrated that the SN, RN and DN were functionally connected to each other, and, in general, their connectivity maps overlapped in a series of subcortical extrapyramidal structures and regions of cerebral cortices. A Granger causality analysis indicated that the effective connectivity graphs within extrapyramidal structures mainly exhibited a spacial up-down pattern for the positive and negative influences, respectively. Our findings suggest that extensive regions involved in the extrapyramidal system constituted a relatively exclusive network via spatial-temporal correlation signals that analogously corresponded to the anatomical structures. The investigation of extrapyramidal system networks may have potential clinical implications.